In vitro inhibition of cytosolic carbonic anhydrases I and II by some new dihydroxycoumarin compounds - (:unkn) unknown (TAYLOR & FRANCIS LTD, 2008)
A new series of 6, 7-dihydroxy-3-(methylphenyl) chromenones, including three new derivatives, i.e. 6,7-dihydroxy-3-(2-methylphenyl)-2H-chromen-2-one (OPC); 6,7-dihydroxy-3-(3-methylphenyl)-2H-chromen-2-one (MPC); 6,7-dihydroxy-3-(4-methylphenyl)-2H-chromen-2-one (PPC) and one previously described, namely 6,7-dihydroxy-3-phenyl-2H-chromen-2-one (DPC), were synthesized. These compounds were investigated as inhibitors of human carbonic anhydrase I (hCA-I) and human carbonic anhydrase II (hCA-II) which had been purified from human erythrocytes on an affinity gel comprised of L-tyrosine-sulfonamide-Sepharose 4B.
Keywords: carbonic anhydrase; isozymes I and II; inhibitors; coumarin; phenols; cancer; ANTITUMOR AGENTS; COUMARIN; SULFONAMIDES; BINDING; ANTIBACTERIAL; DERIVATIVES; ANTIFUNGAL; EXPRESSION; THERAPY; CELLS